Egyptian hieroglyphs for complete beginners : the revolutionary new approach to reading the monuments - Manley, Bill (London : Thames & Hudson, 2012)
Teaches how to translate Egyptian hieroglyphs into English using a step-by-step procedure that includes the use of photographs and line drawings.
Inscriptions : Stela of Mereri (c.2200 BC) : Sound signs ; Direction of writing ; Vowels and pronunciation ; Determinatives ; How do we know how to read hieroglyphs? ; Signs writing 2 or 3 sounds ; Sound complements ; Unexpected writings ; What is transliteration? -- Another Stela of Mereri (c.2200 BC) : The offering formula ; 'a' and 'the' ; Even more unexpected writings ; Ideograms? ; What is Middle Egyptian? -- Stela of Minuser (c.2200 BC) : Word order -- Funerary stamp of Mermose (c.1350 BC) -- Inner coffin of Khnumhotep, son of Nebtu (c.1800 BC) : More about the offering formula ; Identity -- Stela of Dedu and Satsobk (c.1900 BC) : Feminine words ; Why food offerings? -- Stela of Ty (c.2200 BC) -- Stela of Intef and Nesumontju (c.1700 BC?) : Titles of Osiris -- Stela of Shenwy and Hedjret (c.1900 BC) : The dedication formula ; The family -- Coffin of Khnumhotep, son of Henib (c.1850 BC) -- Kings' names : Kings' Titularies -- Stela of Djet, from his tomb at Abydos (c.2950 BC) -- Stela of Raneb (c.2750 BC) ; Inscription of Khakaura Senusret III (c.1836-1818 BC) : Writing plurals -- Another inscription of Khakaura Senusret III (c.1836-1818 BC) -- Three inscriptions of Ramesses II (c.1279-1213 BC) -- Three stelae of Thutmose IV (c.1400-1390 BC) from the Great Sphinx : Epithets ; The king and the gods -- Inscriptions from a golden shrine of Tutankhamun (c.1332-1322 BC) -- The oldest texts and earliest hieroglyphs : How did writing begin in Egypt? -- Slate palette of King Narmer from the Temple of Horus (c.2950 BC) -- Ivory comb of King Djet from his tomb (c.2950 BC) -- Ivory label of King Den from his tomb (c.2900 BC) -- Putting it all together : two inscriptions -- Marriage inscription of Amenhotep III (c.1390 BC) : 'he is' or 'she is' -- Offering-chapel of Sarenput II at Aswan (c.1850) -- Epilogue -- List of kings' names -- List of gods -- List of hieroglyphic signs -- List of words in hieroglyphs.
"New step-by-step method"--Cover.
"47 illustrations."
Includes index.
Keywords: Egyptian language -- Writing, Hieroglyphic; Egyptian language -- Textbooks for foreign speakers -- English; Egyptian language -- Self-instruction.; Hieroglyphics